The Developing a Guessing Game to Improve Speaking Skills for Grade 9th In Mts Al-Hidayah Sukonolo Bululawang: English - Rizqi Yatul Layli; Siti Rofi’ah; Istina Atul Makrifah (Prodi Tadris Bahasa Inggris, 2024)
The study aims to develop a guessing game in English to improve the speaking ability of grade 9 students at MTs Al-Hidayah Sukonolo. This product was developed as a fun learning media for students, so that students can enjoy speaking English, researchers took this product because according to the results of observations and suggestions from the subject teacher concerned. Students also lack confidence when speaking. They are afraid of making grammatical or pronunciation mistakes. The purpose of this study is to improve students. Ability to speak English, with this product students will be trained to be confident in pronouncing words in English based on research and development Borg and Gall. Qualitative data analysis procedure in form of data collection is done by means, of observation, reduction and categorization of data, data appearance a conclusion. Quantitative data analysis was carried out by collecting data from questioner assessment, the second questioner for the validator is material experts, media experts and response questioner given to teacher and students. seeing from questioner and research that has been done that this guessing game product has a score of 61-80% in the sense of good. So, it can be used easily and interestingly for pupils studying English, particularly with regard to their speaking abilities. At the development stage, researchers conducted validation to test the feasibility of the guessing game product. The validation was carried out by two specialists, namely media experts and learning experts. The validation score computation's findings indicate that the final average score, which is 91,07 with extremely valid. Based on the results of the questionnaire analysis that was filled in by students, the final average result was 75,00%. These results indicate the qualification of